Karen Finley's Performance and Judith Butler's Performative: Subverting the Binary Logic of Theatrical Functions - Hardie, Rebecca (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This paper argues that the feminist performance art of Karen Finley challenges the terms Judith Butler sets between performance and performativity and concludes that Finley's art engages in a social, cultural and political critique whereby she determines a new set of codes for her performances.